The Impact of Socioeconomic Status and Parental Involvement on Academic Achievement Role of Stress as A Mediator - Munazza Hayat Rao; Fatima Zafarullah; Aizaz Haider (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
The purpose of this research is to examine the impact of socio-economic status on academic achievement. Moreover, to examine the impact of parental involvement on academic achievement. Furthermore, to examine the mediating role of stress between socio-economic status and parental involvement on academic achievement. The current research design is quantitative in nature, grounded in a positivist philosophy. The population of this study consisted of students studying in Thal University Bhakkar, with a total population of 6,000. The sample size of the current research is 300 students studying in Thal University Bhakkar. The simple random sampling technique was used in this research. Researchers used SPSS and Smart PLS SEM for data analysis. The findings of the current research show that there is a significant effect of socio-economic status on academic achievement. The findings also show that there is a significant role of parental involvement on academic achievement. Lastly, the findings show that there is a significant mediating role of stress between socio-economic status and parental involvement on academic achievement. Schools can help all students to better their academics, especially those facing financial and emotional challenges.